Identification of stock market manipulation: a case study - Simpson, John; Lakshman, Alles; Evans, John; Westaway, Jennifer (Business Perspectives, 2008)
This paper is based on an actual witness report undertaken by university business academics for a corporate regulatory authority in a developed country. The paper describes the methodology used to identify cases of stock market manipulation by insiders of a no liability mining company. An actual data set has been analyzed but the company and the country remain anonymous. It should be added that the real parties originally under suspicion were in fact charged with stock market manipulation based on the actual expert witness report outlined in this paper.